Oral History and Archives in the New South Africa: Methodological Issues - Klopfer, Lisa (Archivaria, 2001)
The upsurge of interest in oral history in South Africa raises a series of methodological questions for archivists. Existing approaches to oral history, whether folkloric, historical, or more focussed on community and identity, have rarely asked whether oral histories should function as records and, if so, how they should be appraised. This essay explores these questions and concludes with a call for more flexible, creative approaches to appraising oral histories.